A = 2/3 – 4/5 , B = 4/5 – 2/3 simplify A and B and verify B is the additive inverse of A .
Answers
Answered by
0
Step-by-step explanation:
2/3 * 3/5 + 5/2 – 3/5 * 1/6 (ii) 2/5 * (3/-7) – 1/6 * 3/2 + 1/14 * 2/5
Answer:
(i) -2/3 * 3/5 + 5/2 – 3/5 * 1/6
= -2/3 * 3/5 – 3/5 * 1/6 + 5/2 [Using associative property]
= 3/5 * (-2/3 – 1/6) + 5/2 [Using distributive property]
= 3/5 * {(-4 - 1)/6} + 5/2 [LCM (3, 2) = 6]
= 3/5 * (-5/6) + 5/2
= -3/6 + 5/2
= -1/2 + 5/2
= (-1 + 5)/2
= 4/2
= 2
Answered by
0
Answer:
gucggiiv 1 ग
Similar questions